2008
DOI: 10.1089/met.2008.0005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Pakistan

Abstract: Over the past two decades, there has been a striking increase in the number of people with metabolic syndrome. The prevalence of metabolic syndrome varies due to lack of an internationally agreed upon definition. Considering the increased cardiovascular risk among Asian people, a lower cutoff for waist circumference is defined. Obesity in terms of waist circumference is found to be 46-68% of the Pakistani population, with a strong association found between arm fat and insulin insensitivity. In studying dyslipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 17 publications
4
54
1
Order By: Relevance
“…The association of age with the disease is highly significant as the P value is < 0.01. The mean value of age in the cases is 47.66 ± 1.2 and this is congruent with a previous local study in which the mean age was 45 ± 15 (22). There is no significant difference in the mean weight of the cases and controls (p-value 0.09).…”
Section: Discussionsupporting
confidence: 90%
“…The association of age with the disease is highly significant as the P value is < 0.01. The mean value of age in the cases is 47.66 ± 1.2 and this is congruent with a previous local study in which the mean age was 45 ± 15 (22). There is no significant difference in the mean weight of the cases and controls (p-value 0.09).…”
Section: Discussionsupporting
confidence: 90%
“…The same type of finding was observed by the researcher of our neighboring countries. 5,12 -This similarity might be due to sharing similar type of lifestyle and socioeconomic status. The study on the population of native Alaska showed the prevalence of metabolic syndrome to be 23.70%).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, low HDL-C level (83.23%) was the most common abnormality causing dyslipidemia. Basit and Shera reported low HDL-C levels in 68-81% of the Pakistani population [29]. The predominance of atherogenic dyslipidemia, glucose intolerance, thrombotic tendency, subclinical inflammation, and endothelial dysfunction among Asians in comparison to Caucasians has been reported [24].…”
Section: Discussionmentioning
confidence: 99%